Modifikasi Perencanaan Pondasi Borepile Sebagai Alternative Pengganti Pondasi Minipile Proyek Gedung Madrasatul Qur’an Jombang - Romadhon Tri Anggoro; Totok Yulianto; Meriana Wahyu Nugroho; Titin Sundari (Fakultas Teknik Universitas Cenderawasih, 2023)
The Borepile Foundation and the Implementation Method for the Madrasah Aliyah Madrasatul Qur’an Tebuireng Jombang Building Project, is one of the deep foundation. The use of borepile foundation is an alternative to minipile foundation. Calculation of building weight using the SAP2000 program. The points reviewed are points S-1 and points S-2. Pile bearing capacity analysis using the Mayerhoff method. By using sondir soil evidence (CPT). The construction of the Madrasah Aliyah Madrasatul Qur’an Tebuireng uses a diameter of 80 cm for borepiles with a depth of 11 m and has 23 D22 reinforcement. There are 4 types of pile caps in the borepile. The dimensions of each pile cap, namely PC-1, PC-2, and PC-4, are 150 cm x 150 cm, while PC-3 is 150 cm x 100 cm. For reinforcement in the x-axis direction of 22 D22 – 150 mm, reinforcement in the y-axis direction of 24 D22 – 160 mm. In the implementation method using a mini borepile because it considers aspect of heavy equipment mobilization. Some of the work in progress includes measuring, making reinforcement, drilling, installing reinforcement, casting, and making pile caps.